2010
DOI: 10.1111/j.1524-4725.2010.01619.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Preoperative and Intraoperative Skin and Nail Surgical Preparation of the Foot in Reducing Bacterial Load

Abstract: Incorporation of intraoperative irrigation of sterile saline solution after nail avulsion surgery reduces potential bacterial load. Every effort should be made to lower the risk of contamination after nail plate avulsion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…The lack of bactericidal efficacy we observed for CHG is consistent with research showing CHG's poor antiseptic performance in surgical preparation hand [ 18 ] and toenail scrubs. [ 24 , 25 , 30 ] However, Marchetti and colleagues found that hand-rubbed CHG (Hisbiscrub) was an effective antiseptic and met the EN 12791 standards.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of bactericidal efficacy we observed for CHG is consistent with research showing CHG's poor antiseptic performance in surgical preparation hand [ 18 ] and toenail scrubs. [ 24 , 25 , 30 ] However, Marchetti and colleagues found that hand-rubbed CHG (Hisbiscrub) was an effective antiseptic and met the EN 12791 standards.…”
Section: Discussionmentioning
confidence: 99%
“…Cotton-tipped swabs have been used for bacterial sampling on skin of the foot and ankle previously. [ 23 26 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that eradicating bacteria from the nail folds and web spaces of the foot is particularly difficult, with a positive aerobic bacterial culture rate remaining greater than 70% for specimens from feet treated with standardized preparation methods involving povidone–iodine 6,7 . While the use of an effective pre‐operative skin‐preparation method is an important step in limiting surgical wound contamination and preventing infection, we believe an intraoperative antiseptic scrub is also of additional importance, due to the recontamination after nail removal that often occurs 8 …”
mentioning
confidence: 97%